2000
DOI: 10.1046/j.1464-410x.2000.00413.x
|View full text |Cite
|
Sign up to set email alerts
|

The histological extent of the local spread of carcinoma of the penis and its therapeutic implications

Abstract: Objective To explore the possibility of reducing the margin of clearance at surgery for carcinoma of the penis without causing an increase in the incidence of local tumour recurrence, so that the functional and cosmetic compromise associated with penectomy might be minimized. Patients and methods Sixty-four patients underwent partial or total penectomy based on the extent of tumour. The specimens were evaluated histologically for grade and for proximal microscopic extensions beyond the grossly visible tumour m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(53 citation statements)
references
References 13 publications
0
47
0
6
Order By: Relevance
“…The traditional 2 cm excision margin has been questioned, and a margin of only a few millimetres is now considered sufficient in selected cases [11][12][13][14]. Negative surgical margins are the "gold standard" in the treatment of penile cancer, although the width of the negative surgical margin does not seem to be an independent prognostic marker [14].…”
Section: Discussionmentioning
confidence: 99%
“…The traditional 2 cm excision margin has been questioned, and a margin of only a few millimetres is now considered sufficient in selected cases [11][12][13][14]. Negative surgical margins are the "gold standard" in the treatment of penile cancer, although the width of the negative surgical margin does not seem to be an independent prognostic marker [14].…”
Section: Discussionmentioning
confidence: 99%
“…As the average length of the glans is ~4 cm (26), local excision of tumors with a size >3 cm may result in a tumor-free margin of <1 cm. Agrawal et al (4) observed an absence of grade 1-2 penile SCC that extended 1 cm beyond the gross tumor margin; however, 25% of grade 3 lesions were histologically positive at 1 cm (4). In these patients with larger tumors, glansectomy with reconstruction is a better alternative to achieve satisfactory oncological and functional outcomes (27).…”
Section: Prior To Matching Subsequent To Matching -------------------mentioning
confidence: 99%
“…5,9,10-12 Indeed, many reports have shown similar 5-year disease-specific survival rates, reducing the width of the resection margins to 10 and 15 mm for grade 1-2 and 3 lesions, respectively. 9,11,13,14 If tumor recurrence occurs, it is usually systemic at the inguinal lymph nodes. In our series of patients treated with total glansectomy, only one patient had inguinal lymph node metastases 18 months after surgery, whereas none had local relapse, and our crude disease-specific survival rate of 93.3% after a mean follow-up of 36 months is similar to that reported by others using conventional surgical treatment.…”
Section: Figurementioning
confidence: 99%